ЕPIDEMIOLOGICAL FEATURES OF PARASITIC DISEASES - Fakhriddinova Sh.F. (PEDAGOGS, 2025)
Summary. Helminthiasis constitutes the largest group of parasitic diseases. They are caused by parasitic worms or helminths. More than 250 species of helminths have been registered in humans. Of this number, about 30 are common human parasites and form foci with significant infestation, and the rest are animal helminths that infect humans more or less accidentally.